Competencies Principal of the Islamic School - Wulandari, Novi (International Conference of Moslem Society, 2019)
The principal of the Islamic school (madrasah) as the leader of an educational institution is a activator, direction setting of school policies tha will set how the school aims and education in general. Therefore, the principal has a very large role in the scope of the school, especially in improving teacher competence. So the principal as a leader in an educational institution has a big role in movingsubordinates, starting from educating, leading, managing, supervising and making improvements to their subordinates. It is done to maintain and improve the competencies of educators. To create the quality of proofessional human resources, the principal must have a precise strategy, such as; education supervision, education and training, giving continuous motivation, changing work culture, in order to the teacher competence as a basic element of educators can be realized. These competencies include; pedagogic competence, personal competence, social competence, professional competence.